Microbiologically Influenced Corrosion of Carbon Steel Beneath a Deposit in CO2-Saturated Formation Water Containing Desulfotomaculum nigrificans - Liu, Hongwei; Meng, Guozhuo; Li, Weihua; Gu, Tingyue; Liu, Hongfang (Frontiers in Microbiology, 2019)
The corrosion mechanism of carbon steel under deposit in the presence of sulfate reducing bacterium (SRB) Desulfotomaculum nigrificans was studied using surface analysis, weight loss and electrochemical measurements. Results showed that both the general corrosion and localized corrosion were considerably promoted by SRB under deposit. The corrosion rate of steel in the presence of SRB was approximately 6 times of that for the control according to the weight loss measurements. The maximum corrosion pit depth in the presence of SRB was approximately 7.7 times of that of the control. Both the anodic and cathodic reactions were significantly accelerated by SRB. A galvanic effect in the presence of SRB due to the heterogeneous biofilm led to serious localized corrosion.